Impact of COVID-19 on clinical outcomes and care delivery in pediatric oncology patients in Lebanon in 2020–2023: a retrospective study - Noun, Peter; Farhat, May; Khalife, Hassan; Younis, Jennifer Bou; Farhat, Mohamad; Kabbout, Hadi; Haridy, Hammam; Moussa, Jihane; Lefebvre d’Hellencourt, Florence; Rao Valluri, Srinivas; Spinardi, Julia; Al Akoury, Nadine; et al. (Frontiers in Pediatrics, 2025)
IntroductionThe COVID-19 pandemic has significantly impacted the pediatric population worldwide, particularly those with comorbidities who often experience more severe outcomes. However, the impact of COVID-19 on pediatric oncology patients remain poorly understood.MethodsThis retrospective observational study examined data from 85 pediatric oncology patients aged <18 years who tested positive for COVID-19 at five study sites across Lebanon from March 2020 to May 2023. Detailed demographic, clinical, treatment, healthcare resource utilization (HCRU), and disease outcomes were collected. Outcomes was summarized descriptively and two-sided 95% confidence intervals (CI) were calculated using the Clopper-Pearson method.ResultsThere was 85 pediatric oncology patients diagnosed with COVID-19, with a mean age of 11.57 years. Of these, 72 patients (84.6%) had hematological malignancies and 13 (15.4%) had solid tumors. Thirteen patients (15.3%) had comorbidities. Treatment delays on oncology care occurred in 61 patients (71.8%). Twelve patients (14.1%) required hospitalization, four of whom needed intensive care unit (ICU) admission, with ICU stays ranging from 1 day to 2 months. COVID-19 related mortality was 4.7%.DiscussionCOVID-19 was associated with changes or delay in oncological treatment. In addition, the burden of COVID related hospitalization, intensive care utilization and death were substantial among pediatric cancer patients. Our findings highlight the importance of vaccination in pediatric oncology patients.